Study about eating habits of higher education students - Florença, Sofia G. (2019)
Introduction: The transition from secondary school to university is associated with many changes, at the social and surrounding influences’ levels, which may be a risk factor for unhealthy lifestyles. It is known that the years spent at the university may be associated with poor eating habits, with levels of fast-food consumption higher than desirable, possibly low intake of fruits and vegetables and breakfast skipping, among others. Objective: This study investigated some eating habits in a sample of students frequenting higher education establishments in the Centre of Portugal. Methods: It was carried out a questionnaire survey of self-response to investigate some of the eating habits of the participants. The questionnaire was applied after all ethical issues were guaranteed and after approval by the ethical committee. The number of valid questionnaires obtained was 670. Results: In the sample evaluated, most of the students revealed satisfactory eating habits, with significant differences between age groups, the area of studies and the practice of high competition sport. A considerable percentage of the participants, 40.8%, ate 5 meals per day and only 0.6% ate less than 3 meals per day. Only 6.6% of the participants indicated that usually do not eat breakfast. In general, the participants’ breakfast included milk (54.0% of positive answers), bread (45.8% of positive answers), cereals (32.7% of positive answers) and coffee (23.9% of positive answers). Regarding lunch, 30.1% of the participants ate soup, 28.4% consumed vegetables, 28.2% ate pasta, 21.6% fish, 16.0% potatoes, 2.5% yoghurt, 15.5% soft juices, 4.3% juices, 23.6% salad, 10.4% chips, 58.2% meat, 38.5% rice, 27.8% fruit, 9.4% a sweet desert and 44.9% drank water. Conclusions: The results pointed to the necessity of improving educational programs which can contribute to improve university students’ eating habits.